Analisis Kemampuan Berpikir Komputasi Menggunakan Software Matematika Photomath - Hidayati, Nadia; Yahfidzham (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research discusses the analysis of students’ computational thinking abilities using Photomath mathematics software. This research was conducted with the aim of finding out how Photomath can help students improve their computational thinking skills. The research results show that Photomath can help students improve their computational thinking skills if used effectively and not misused. Photomath can help students solve math problems in a more effective and efficient way. Thus, Photomath can be a useful tool in improving students’ computational thinking skills.